2019
DOI: 10.1073/pnas.1812257116
|View full text |Cite
|
Sign up to set email alerts
|

Green fluorescence from cnidarian hosts attracts symbiotic algae

Abstract: SignificanceReef-building corals cannot survive without symbiotic algae, Symbiodinium, on which they depend for most of their energy. Most coral species gain symbionts from the environment early in life, and possibly after bleaching (i.e., the loss of symbionts in response to stress). However, Symbiodinium density on coral reefs is very low. Although it has long been hypothesized that corals must be able to attract free-living Symbiodinium, such a mechanism has yet to be identified. Here, we use a series of ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
54
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(59 citation statements)
references
References 42 publications
5
54
0
Order By: Relevance
“…Blue light photoreceptors have been implicated as a critical regulator of photoprotection in Chlamydomonas reinhardtii , where they control a negative feedback mechanism on photosynthesis under high irradiance via PSII nonphotochemical quenching (Petroutsos et al, ). In Symbiodiniaceae, negative phototaxis in response to blue light was recently demonstrated (Aihara et al, ) and has been previously identified in other eye spot‐containing dinoflagellates (Horiguchi, Kawai, Kubota, Takahashi, & Watanabe, ; Ozasa, Won, Song, Shinomura, & Maeda, ), suggesting avoidance of blue light spectra may be an adaptive behaviour in dinoflagellates. We suggest that host attenuation of blue light represses the transcriptional activation of dinoflagellate blue light photoreceptors in hospite.…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…Blue light photoreceptors have been implicated as a critical regulator of photoprotection in Chlamydomonas reinhardtii , where they control a negative feedback mechanism on photosynthesis under high irradiance via PSII nonphotochemical quenching (Petroutsos et al, ). In Symbiodiniaceae, negative phototaxis in response to blue light was recently demonstrated (Aihara et al, ) and has been previously identified in other eye spot‐containing dinoflagellates (Horiguchi, Kawai, Kubota, Takahashi, & Watanabe, ; Ozasa, Won, Song, Shinomura, & Maeda, ), suggesting avoidance of blue light spectra may be an adaptive behaviour in dinoflagellates. We suggest that host attenuation of blue light represses the transcriptional activation of dinoflagellate blue light photoreceptors in hospite.…”
Section: Discussionmentioning
confidence: 76%
“…This may be indicative of differences between the free‐living and in hospite environments. Whereas in hospite cells persist within a symbiosome inside of a host, free‐living cells must navigate in space and respond to a diverse array of changing environmental cues such as light (Aihara et al, ; Hollingsworth, Kinzie, Lewis, Krupp, & Leong, ) and chemicals (Fitt, ; Pasternak, Bachr, Abelson, & Achituv, ). On the other hand, the niche occupied by dinoflagellate endosymbionts in coral‐algal symbioses imposes a very particular set of functional requirements on the endosymbiont, which probably requires a reduced signalling repertoire.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ability of individual juveniles to gain and maintain novel symbionts through horizontal acquisition might provide a crucial mechanism to increase the chances of survival in a new environment during dispersal at the larval stage (Byler et al, 2013) and, at the same time, the inheritance of symbionts from the parents would assure the supply of photosynthetic products during the delicate initial larval stages. Previous studies have shown that different clades of Symbiodinium have differential preferences for the light intensity required for photosynthesis and that they are differently affected by the host internal light environment variation, which can be achieved through the modulation of the GFPs fluorescence intensity (Ezzat et al, 2017;Quigley et al, 2018;Aihara et al, 2019). Since the light intensity necessary to attract specific symbionts likely differs with light spectra and depth (Aihara et al, 2019), coral larvae from shallow and deep reefs potentially generate diverse internal light environments, displaying different GFP fluorescence depending on the preferred association with different Symbiodinium clades (Yuyama and Higuchi, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…However, the present study suggests that GFP expression in P. damicornis juveniles increased in re sponse to bleaching stress. Recently, Aihara et al (2019) demonstrated that algal symbionts were attracted to green fluorescence emitted by both endogenous GFP of live coral fragments and an artificial green fluorescence dye.…”
Section: Effects Of Environmental Stress On Green Fluorescencementioning
confidence: 99%